VO.22 – Approval of unit rates of non-schedule item' UPVC pipe changed from PVC pipe for conduit works’ - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the clarification approval of unit rates of non-schedule item' UPVC pipe changed from PVC pipe for conduit works of BRACU new campus project site.